Enhanced nitrate reduction by HPMC-stabilized nanoscale zero-valent iron (H-NZVI): Synthesis, characterization and reaction kinetics - Da Ma; Xusheng Li; Huian Zou; Yi Qian; Mengqi Li; Wenchuan Xu (Desalination and Water Treatment)
Nano zero-valent iron (NZVI) was successfully stabilized by using hydroxypropyl methyl cellulose (HPMC). Systematic characterization observations (including XRD, TEM, FTIR, and VSM), as well as settling performance, illustrated that, compared to bare nano zero-valent iron particles (NZVI), the dispersity and antioxidizability of HPMC-stabilized nanoscale zero-valent iron particles (H-NZVI) were improved. Nitrate reduction efficiencies by using iron powder, NZVI, H-NZVI-5, H-NZVI-10, and H-NZVI-20 were examined, and the results showed that a moderate amount of HPMC in modification can help prevent the aggregation of NZVI and achieve high reduction efficiency. Excessive HPMC in preparation led to a decline in reduction efficiency. In addition, effects of initial pH, dissolved oxygen concentrations, and reaction temperatures on nitrate removal were studied. The results showed that the efficiency decreased with increases in initial pH and dissolved oxygen concentrations. However, the stabilized NZVI showed great superiority to bare NZVI, maintaining high activity even at basic pH or aerobic conditions. Pseudo first-order kinetics was applied to study nitrate reduction kinetics and confirmed to correlate well with experimental data. Through analysis of rate constants at different temperatures, the apparent activation energy for nitrate reduction by H-NZVI-10 was calculated to be approximately 15.18 kJ/mol. This study demonstrates that HPMC-stabilized NZVI can serve as a promising nanomaterial for enhancing nitrate reduction of nitrate.